Case report: Myocarditis following COVID-19 protein subunit vaccination - Dong, Yi-ming; Liu, Xia; Yang, Chen-teng; Qi, Qian; Shi, Wei-bo; Li, Ying-min; Zuo, Min; Wang, Song-jun; Bi, Hai-tao; Ma, Ru-fei; Zhang, Guo-zhong; Cong, Bin (Frontiers in Cardiovascular Medicine, 2022)
We report findings in a 34-year-old female patient who presented with fulminant myocarditis 8 days after receiving the first dose of the ZF2001 RBD-subunit vaccine against coronavirus disease 2019 (COVID-19). Autopsy showed severe interstitial myocarditis, including multiple patchy infiltrations of lymphocytes and monocytes in the myocardium of the left and right ventricular walls associated with myocyte degeneration and necrosis. This report highlights the details of clinical presentations and autopsy findings of myocarditis after ZF2001 (RBD-subunit vaccine) vaccination. The correlation between vaccination and death due to myocarditis is discussed.